KEMAMPUAN NUMERIK SISWA SEKOLAH MENENGAH ATAS DALAM PEMECAHAN MASALAH MATEMATIS - Viktorianus Ipik; Yulis Jamiah; Ahmad Yani T (Jurnal AlphaEuclidEdu, 2022)
This article is the result of a qualitative descriptive analysis to describe and describe students' mathematical reasoning abilities in problem solving in class VIII G SMP Negeri 3 Sungai Raya. The research subjects were 32 students. Data collection tools are in the form of mathematical reasoning tests on statistical material, especially in the sub-material of data presentation and data concentration steps as well as interview guidelines. The results of data analysis showed that based on the category of upper, middle and lower level of reasoning ability, it was classified as moderate because there were 2 students (6.25%) in the upper level reasoning category, then there were 18 students (56.25). %) in the intermediate level reasoning category. , and 12 students (37.5%) were included in the lower-level reasoning category. Students with upper level abilities are able to fulfill indicators of applying numerical mathematics, check the validity of a contradiction, and provide reasons or evidence for the accuracy of the arrangement, students with intermediate abilities are able to meet indicators of applying numerical mathematics and provide reasons or evidence for the accuracy of settings, students with high level abilities bottom height can only meet the indicators of applying numerical mathematics.